STEROID FOR MANAGEMENT OF PSEUDO-OTHEMATOMA - Sudana, Wayan; Adiputra, Nyoman; Wiyadi, H.M.S. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 5, No. 1 Januari 2011)
Has conducted research on the use of steroids triamsinolon asetonid as pseudo-othematomamedical therapy. The purpose of this study was to determine the effectiveness triamsinolonasetonid. Prevention of the formation of serum in the lesion, so that pseudo-othematomacan be cured without surgery. Surgery and preventing of the formation collagen tissue inthe lesion, so that the pseudo-othematoma can be cured without deformity. It is expectedthe establishment of a pseudo-othematoma practical for health personnel, effective,efficient, safe and comfortable for the patient. This study design is the design of arandomized controled pretest-postest design. In the test group were treated withtriamsinolon asetonid intracutaneus injected in lesion area with the number according tothe percentage of the amount of teraphy effusion before. Then press verban installed. In thecontrol group, only pressing verban installed. From the research results obtained, whishafter the third treatment using the triamsinolon asetonid, pseudo-othematoma diseaselooked very meaningful. Due to its unique histological structure of the ear, then themanipulation of the ear is moe advisable to be careful, to prevent new lession with variousimpacts.
Keywords: Steroids, Management, Pseudo-othematoma